2019
DOI: 10.1017/sjp.2019.18
|View full text |Cite
|
Sign up to set email alerts
|

A Psychometric Assessment of a Human Resources Practice Measure for Temporary Agency Workers

Abstract: Studies have proposed and validated several measures that evaluate employee’s perceptions of the human resources practices (HRP). However, given the changes occurring in the labor market, there is a need to develop a measure specially adapted to the contingent workers specific employment relationship. Thus, this study assesses an HRP system scale that was administered to temporary agency workers (TAW) to examine the scale’s response process, internal structure and relation to other variables (i.e., affective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Specifically, TAWs perceive HRP investments have an impact on their relationship with the agency and with client companies, regardless of which client company provides them. This is in line with recent research where HRP investments by one employer reinforces the positive perceptions TAWs have on other client employers (Buch et al , 2010; Connelly et al , 2011; Coyle-Shapiro and Morrow, 2006; Sobral et al , 2019). Client companies can therefore elicit stronger affective commitment from TAWs if they jointly provide HRP and mutually reinforce each other’s efforts, resulting in better work outcomes and performance (Coyle-Shapiro and Morrow, 2006).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Specifically, TAWs perceive HRP investments have an impact on their relationship with the agency and with client companies, regardless of which client company provides them. This is in line with recent research where HRP investments by one employer reinforces the positive perceptions TAWs have on other client employers (Buch et al , 2010; Connelly et al , 2011; Coyle-Shapiro and Morrow, 2006; Sobral et al , 2019). Client companies can therefore elicit stronger affective commitment from TAWs if they jointly provide HRP and mutually reinforce each other’s efforts, resulting in better work outcomes and performance (Coyle-Shapiro and Morrow, 2006).…”
Section: Resultssupporting
confidence: 91%
“…Perceptions of the HRP system was measured using a 20-item scale. The scale was adapted, tested and validated with Portuguese TAWs by Chambel et al (2016) and Sobral et al (2019). According to Sobral et al (2019) because each HRP is not independent, this scale examines how TAWs perceive HRP regardless of the company providing these practices (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Perceptions of the HRP system was measured using a 20-item scale (α = 0.87) that measured TAW’s socialization, recruitment, training (i.e., promotion of internal and external employability), and performance appraisal [ 54 , 55 ]. This scale was adapted, tested and validated with TAW by Sobral and colleagues [ 56 ], and was previously tested with Portuguese TAW [ 44 ]. According to the authors [ 56 ], because each HRP is not independent, this scale examines how TAW’s perceive HRP regardless of the company providing the practices (i.e., agency or client company).…”
Section: Methodsmentioning
confidence: 99%
“…This scale was adapted, tested and validated with TAW by Sobral and colleagues [ 56 ], and was previously tested with Portuguese TAW [ 44 ]. According to the authors [ 56 ], because each HRP is not independent, this scale examines how TAW’s perceive HRP regardless of the company providing the practices (i.e., agency or client company). It is believed that the agency and the client are jointly responsible for the HRP system; thus, TAW’s overall perceptions were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Shah [34] proposed a model comprising seven GHRM practices: green compensation management, green health and safety, green job design, green labor relations and green performance management, green recruitment and selection and green training and development. Although no studies were found regarding green HRM practices in Portugal, research focused on employees' perceptions of HR practices [8] and its antecedents and outcomes [35,36].…”
Section: -1-green Human Resources Managementmentioning
confidence: 99%